Women on Board: The Blank Space of ESG Impact in Indonesia - Kristianti, Ika Puspita (Jurnal Akuntansi dan Perpajakan, 2024)
This research analyzes the impact of board gender diversity and industry classification on ESG performance in Indonesia. It also seeks to gather evidence on the extent to which ESG risk affects financial and market performance. Considering the unique context of gender equality in Indonesia and the expectation that gender differences influence decision-making processes in financial reporting, this study examines the impact of women on boards on financial and stock market performance, with ESG Risk as a mediator. This study employs a quantitative approach and applies purposive sampling method to select a sample of population, consisting of companies listed on the Indonesia Stock Exchange (IDX). This research uses Smart PLS to analyze the data, including tests of the measurement model and structural model. The results indicate that board gender diversity and industry classification have a significant negative impact on ESG Risk Rating, and ESG Risk Rating impact positively to stock performance. This research provides valuable and original contributions to the understanding of ESG practices, board gender diversity, and their impact on financial and market performance in Indonesia, which addresses gaps in the literature and offers practical implications for companies, investors, and policymakers in emerging markets.